Improving Gas Bubblesâ€™ Half Life in Foam Drilling Fluid (Jurnal Teknologi (Sciences & Engineering), 2013)
An underbalanced drilling using foam drilling fluid is one of the most effective solutions which are capable of preventing formation damage, differential sticking, or circulation lost. Nevertheless, the limitation of using foam drilling fluid is the stability of its rheological properties which would affect its lubricity characteristics. Therefore, a research study was carried out to determine the stability and effectiveness of water soluble polymers as an additive in foam drilling fluid. To produce the required and most stable foam, four types of surfactants had been tested, namely sodium dodecyl sulfate (anionic), cetyltrimethylammonium bromide (cationic), TÃ—100 (non ionic), and n-alkyl betaines (amphoteric). Then, the water soluble polymers, namely xanthan gum, hydroxyethyl cellulose, guar gum, and carboxymethyl cellulose, were evaluated as a stabilizer in the said foam drilling fluid. The laboratory works involved lubricity and rheological properties tests, which were conducted at ambient condition. The experimental results showed that the use of xanthan gum with anionic surfactant produced the most stable foam drilling fluid compared to other polymers. Rheological properties of the polymer foam drilling fluid were compared with water-based mud, and it was revealed that polymer foam drilling fluid could perform as effective as the latter. The significant advantage of using polymer foam drilling fluid was its coefficient of friction which was found to be lower than the water-based mud.Â